Keluar Rumah pada Malam Hari dan Penggunaan Kelambu Berinsektisida dengan Penyakit Malaria di Desa Lempasing - Dea Selvia (Jurnal Ilmiah Kesehatan (JIKA), 2019)
Malaria is an infectious disease caused by Plasmodium sp and is transmitted through a mosquito bite Anopheles females. Malaria is on of the diseases established in the Sustainable Development Goal (SDGs) which is the continuation of the Millennium Development Goals (MDGs) with the target to be denied in 2030. Malaria can occur due to the interaction between the environment, the individual and the Anopheles mosquito as a Plasmodium Sp carrier vector. The purpose of the study was to know the relationship Outdoors Activity on The Night and use of insecticidal nets with malaria in Lempasing village. Type of analytic studied with cross sectional approaches. Data collection used validated questionnaire. The number of subject in this study was 30 subjects. The statistical analysis used Chi Square Test. The results showed that there was an out-of-home relationship at night (p = 0,028) and the use of mosquito netting (p = 0,008) with malaria in Lempasing village. It is suggest to people in Lempasing village to don’t go out of the house in the night and use insecticidal nets to avoid malaria.